The impact of digitalization on marketing communications measurement process : case of global B2B industrial companies - Järvinen, Joel (2011)
The stature of marketing communications function is under a threat within the firms. As the board of management tends to demand the profitability of all business activities, marketing practitioners have for a long time been unable to credibly show the link between marketing communications actions and financial value. Fortunately, the digitalization has offered new insights and opportunities to make the marketing communications actions more measureable. “Everything can be tracked” is an often heard slogan when speaking of monitoring web users’ online behavior facilitated by web analytics software. However, it is questionable how well this slogan fits the marketing communications of Business-to-business (B2B) industrial companies that tend to stress the role of personal selling in their marketing communications activities.